A Descriptive Study on Integrated Public Services through Public Service Malls (MPP): A Good Governance Perspective - Hibali, La Ode Zulfikar; Ramadhan, Syahril; Arsyiah, Wa Ode; Hara, Kuflia Muak (Indonesian Journal of Social Science Research, 2025)
Public service is a fundamental element in the implementation of good governance; however, in practice, Indonesia still faces various challenges such as lengthy bureaucracy, inefficient procedures, and weak inter-agency coordination. To address these issues, the government initiated the establishment of Public Service Malls (MPP) as an innovation in integrated services within a single location, combining services from various sectors. This study aims to describe the implementation of integrated public services through MPP, identify supporting and inhibiting factors in its operation, and analyze its contribution to the application of good governance principles at the regional level. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, document reviews, and simple questionnaires. The findings indicate that MPP enhances the effectiveness and efficiency of services through cross-agency integration and the use of digital technology, although challenges remain in terms of institutional coordination and human resource capacity. Good governance principles such as transparency, accountability, and responsiveness have begun to materialize through more open and measurable service mechanisms. The contribution of this study lies in its empirical understanding of how MPP-based public service innovation can serve as a strategic instrument to strengthen participatory governance oriented toward citizen satisfaction, as well as its conceptual foundation for developing more adaptive and sustainable public service policies.